Principle and Strategy of Rehabilitation Intervention for Inpatients with COVID-19 - Zhouying DUAN; Wenhua CHEN; Ruijuan ZHOU; Yilan SHENG; Fei HE; Jianhua LI (康复学报)
To provide references for safe and effective implementing rehabilitation treatment during hospitalization, in this article, we exploratively discusses the principle and strategy of treatment for inpatients with COVID-19 based on clinical characteristics as infectious pulmonary diseases. The foundation of rehabilitation intervention in COVID-19 is'integration of prevention, treatment and rehabilitation'frame. The earlier the rehabilitation intervention starts, the better the prognosis will be, in the stable stage of the disease. Anoxia is the main clinical manifestation for inpatients with COVID-19. The best intervention point for inpatient's rehabilitation may be resolving the disease-caused anoxia via systemic management approaches safely and efficiently in rehabilitation medicine. Thus, this article proposes that we should keep on the principle, 'No Excess, No Absence', and use the strategy basing on'Energy Conservation and Emission Reduction'as common goal management in the cooperation of multidisciplinary team approach on inpatient of COVID-19 rehabilitation. The series of stabilization, relaxation and energy-saving on'physical-mental level'were the major methods. And meanwhile the interaction among evaluation and intervention on individual and environment at the same time with the inclusion of COVID-19 prevention and control will rule into rehabilitation management process. The rehabilitation intervention on COVID-19 inpatients is not only the technique-oriented but also a systemic management process. The option of health efficacy promotion approaches via systemic vision is the demonstration of the most important concept in rehabilitation medicine, 'People Frist of All'. The cognition on various meaning in rehabilitation medicine will provide new for rehabilitation field.